Content Analysis of Item Songs: Reflections of A Toxic Socio-Cultural Milieu - et. al., Dr. Shivali Sharma, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The present paper is based on the premise that the item songs in bollywood movies are the worst reflections of the identity of women. Movies are a popular form of mass media and they play a key role in moulding opinions, constructing images and reinforcing dominant cultural values. The structure of the "lyrics and the dance moves" in the item songs objectify the females in the most degrading ways. In the present paper content analysis was conducted on 15 Item Numbers over the span of 23 years. Considering the over popularity of the item songs, and its corresponding impact on culture; it is crucial to analyze and interpret the lyrics and dance moves portrayed in the Item Songs. The primary themes of the Top Item Songs were analyzed and they include: the glorification of criminal activities , self objectification, dismemberment, Materialism, high libidinal drive in women, the sexual objectification of women etc.